A study of acoustic emission testing on mild steel MIG welding - Nik Mohamad Yusof, Nik Mahmud (2012)
This project was carried out to study the availability of using Acoustic Emission (AE) technique on mild steel MIG welding. The objective of this research is to investigate the effect of welding joint between two types of mild steel and also to classify different type of signal characteristics occur on defected and non-defected welding joint. Test plans consist of two experiments. Experiment one was conducted to see the signal characters on defected welding joint meanwhile for experiment two for non-defected welding joint. The same procedures were applied for both experiments. MIG welding process was run to joint two plate of mild steel. The sensor then was located at five different positions for both defected and non-defected welding joint to capture the AE waves. The signals of AE were recorded using physical acoustic instrumentation. For all five positions on defected and non-defected welding joint, the value, of hits, counts, peak amplitude, RMS, and rise time were recorded and analysed were using Matlab. The result showed almost all parameters values for defected welding joint were higher compared to the non-defected welding joint. The results also show all parameters value highest at third position for both experiments due to weight of load. The conclusion has shown that the defected welding joint has produced higher number AE signal compared to the non-defected one due to error of stress location or cracks at welding joint.